Cement-free thermal shock resistant cast refractory
Patent Information
- Application Number
- CN202611377373.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]针对现有技术的不足,本发明的目的在于提供一种无水泥抗热震耐火浇注料,以解决现有技术中存在的材料的耐火度、高温蠕变性、抗侵蚀性、热震稳定性不足的问题
[0028]本发明不引入铝酸钙水泥,通过添加不同比例的电熔莫来石、超细稳定氧化锆粉、SiO2凝胶粉、活性双峰Al2O3粉、球形硅微粉以及高性能复合减水剂,避免了铝酸钙水泥在高温下生成大量的钙长石低熔相的弊端,进而克服了传统耐火浇注料耐火度不足、高温易蠕变及热震稳定差的问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallurgy, specifically relating to a cement-free thermal shock resistant refractory castable. Background Technology
[0002] Refractory castables are a typical type of refractory material, possessing advantages such as good integrity, strong resistance to spalling, and flexible construction methods. They are widely used in metallurgy, casting, heat treatment, cement kilns, smelting furnaces, and other fields.
[0003] Currently, most refractory castables on the market use calcium aluminate cement as a binder, which provides good fluidity and low-temperature strength for the castable. However, under high-temperature conditions, the CaO in the cement will react with other components in the castable system to form a large amount of low-melting phases such as calcium feldspar, tricalcium silicate, and calcium aluminum feldspar, which limits the material's refractoriness, high-temperature creep, erosion resistance, and thermal shock stability. This leads to problems such as softening deformation, collapse, spalling, and perforation in linings made of refractory castables. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a cement-free thermal shock resistant refractory castable to solve the problems of insufficient refractoriness, high-temperature creep resistance, erosion resistance, and thermal shock stability of existing materials.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] A cementless thermal shock resistant refractory castable comprises the following raw materials in parts by weight: 25-35 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 20-30 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 15-25 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 5-10 parts of ultrafine stabilized zirconia powder, 1-5 parts of SiO2 gel powder, 5-10 parts of active bimodal Al2O3 powder, 5-10 parts of spherical silica powder, and 0.2-0.6 parts of high-performance composite water-reducing agent.
[0007] Furthermore, it also includes 4 to 5 parts water.
[0008] Furthermore, in the electrofused mullite, the Al2O3 content is >74.0%, the SiO2 content is >20.0%, and the CaO content is ≤0.15%.
[0009] Fused mullite is a commonly used refractory raw material. It has large, complete, and well-developed crystals with small, non-penetrating pores, high purity, good volume stability, and no large amount of free glass phase. In castables, it is used as the main aggregate to construct a high-strength rigid skeleton and has excellent high-temperature strength, thermal stability, and creep resistance.
[0010] Furthermore, in the ultrafine stabilized zirconia powder, the ZrO2+HfO2 content is ≥94.5%, the CaO content is ≤0.01%, and the Na2O content is ≤0.02%; the particle size of the ultrafine stabilized zirconia powder is D50=0.1~0.3 μm, and the specific surface area is 12~18 m² / g.
[0011] Under the influence of thermal shock and tensile stress, ultrafine stabilized zirconia powder undergoes a martensitic phase transformation from t-ZrO2 to m-ZrO2. The accompanying volume expansion offsets the firing shrinkage of the product, resulting in relative volume stability at high temperatures. Simultaneously, it passivates microcracks and improves thermal shock resistance and creep resistance. ZrO2 exhibits excellent chemical stability, rarely reacting with the silicon-aluminum matrix at high temperatures, and no low-melting-point phases are formed. The dense, ultrafine particles fill and block pore penetration channels, effectively inhibiting the erosion and penetration of molten slag and metal, significantly improving the high-temperature performance of the material and extending the service life of the product.
[0012] Furthermore, the SiO2 gel powder has a SiO2 content ≥ 99.8%, a Na2O content < 0.01%, a CaO content ≤ 0.01%, and a particle size ≤ 38 μm.
[0013] The surface of SiO2 gel powder is rich in active silanol groups, which provides demolding strength. At high temperatures, it can form mullite in situ with active alumina (active bimodal Al2O3 powder). The porous structure of the gel forms tiny pores after firing, which can improve the thermal shock resistance of the material. In addition, the powder has extremely low impurity content and no low melting phase is generated, which ensures the high-temperature mechanical strength, creep resistance and resistance to penetration and erosion of the material.
[0014] Furthermore, the active bimodal Al2O3 powder has an Al2O3 content ≥99.8%, a Na2O content <0.08%, and a CaO content ≤0.03%; the active bimodal Al2O3 powder has a particle size of D50=1.4μm and a specific surface area of 4.8 m² / g.
[0015] The active bimodal Al2O3 powder is prepared by blending ultrafine particles with medium-sized sub-fine particles, exhibiting a bimodal particle size distribution. The ultrafine particles primarily provide the aluminum source for mullite formation at high temperatures, while the sub-fine particles not only participate in the solid-phase reaction as an aluminum source but also fill inter-particle gaps and optimize particle packing. The active bimodal Al2O3 powder has a small particle size, large specific surface area, and high reactivity, effectively filling matrix pores and promoting mullite phase formation. The randomly interwoven needle-like and whisker-like mullite crystals form a three-dimensional interlocking framework, which disperses and releases thermal stress generated by sudden temperature changes, improving the high-temperature strength, corrosion resistance, and thermal shock resistance of the product.
[0016] Furthermore, the spherical silicon micropowder has a SiO2 content > 99.6%, a CaO content < 0.03%, and a Na2O content < 0.05%; the spherical silicon micropowder has a particle size of D50 = 0.5 μm and a specific surface area of 12~16 m² / g.
[0017] Spherical silica micropowder is a smooth, solid sphere with rounded, smooth particles and no sharp edges. Its spherical structure provides lubrication, reducing frictional resistance between powder particles, preventing agglomeration, reducing the amount of water or liquid binder required, and improving slurry flow properties. The surface of the micropowder contains a large number of active silanol groups, which can react with the aluminum source (active bimodal Al2O3 powder) at high temperatures to form mullite, synergistically regulating the sintering shrinkage of the material. Simultaneously, the micropowder has high purity, with extremely low levels of impurities such as calcium and iron, preventing the formation of low-melting-point liquid phases, effectively improving the material's density, high-temperature strength, volume stability, and corrosion resistance.
[0018] Furthermore, the high-performance composite water-reducing agent comprises a carboxylic acid polymer and an additive; the mass ratio of the carboxylic acid polymer to the additive is 8:2.
[0019] Furthermore, the carboxylic acid polymer is a comb-like copolymer with a main chain degree of polymerization of 25-45 and a side chain degree of polymerization of >45; the additive is one or more of sodium hexametaphosphate, tripolyphosphate, sodium citrate, polyoxyethylene polyoxypropylene glycerol ether, and polyoxyethylene polyoxypropylene pentaerythritol ether type polyether.
[0020] High-performance water-reducing agents contain high-molecular-weight carboxylic acid polymers that possess both carboxyl and ester groups, exhibiting both hydrophilicity and a degree of hydrophobicity. The electrostatic repulsion of the carboxyl anions effectively disperses the micropowder. Furthermore, due to the hydrophobic main chain and the grafted block structure of the hydrophilic side chains, a stable hydrated isolation layer can be formed on the particle surface, preventing the random agglomeration of the micropowder and maintaining its dispersibility. Sodium hexametaphosphate, tripolyphosphate, and sodium citrate rely on electrostatic repulsion to break up micropowder flocs, while simultaneously chelating Na in the material. + Fe³ + Impurities such as cations prevent the neutralization of carboxyl groups in carboxylic acid polymers, thus avoiding damage to the adsorption layer on the particle surface and ensuring the fluidity of the slurry. Polyoxyethylene polyoxypropylene glycerol ether and polyoxyethylene polyoxypropylene pentaerythritol ether type polyether can suppress bubbles generated during stirring, reduce the porosity inside the castable, reduce apparent porosity, and improve the bulk density and mechanical strength of the castable at room temperature and high temperature.
[0021] A method for preparing a cementless thermal shock resistant refractory castable includes:
[0022] S1. Prepare fused mullite, ultrafine stabilized zirconia powder, SiO2 gel powder, active bimodal Al2O3 powder, spherical silica micropowder, high-performance composite water-reducing agent and water;
[0023] S2. Add fused mullite, ultrafine stabilized zirconium oxide powder, SiO2 gel powder, active bimodal Al2O3 powder, and spherical silica powder to a mixer for premixing to obtain the first premixed material.
[0024] S3. Add the high-performance composite water-reducing agent to a portion of the water and mix it evenly with the first premixed material obtained in step S2 to obtain the second premixed material.
[0025] S4. Add the remaining water to the second premixed material in the mixer until the material reaches the appropriate fluidity and then discharge it.
[0026] The cementless castable of this invention can be used in smelting furnaces, holding furnaces, or molten metal transfer containers, and is mainly suitable for parts that come into contact with molten metal or are susceptible to wear, penetration, and corrosion.
[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0028] This invention does not introduce calcium aluminate cement. By adding different proportions of fused mullite, ultrafine stabilized zirconia powder, SiO2 gel powder, active bimodal Al2O3 powder, spherical silica powder, and high-performance composite water-reducing agent, it avoids the drawback of calcium aluminate cement generating a large amount of low-melting phase of anorthite at high temperatures. This overcomes the problems of insufficient refractoriness, easy creep at high temperatures, and poor thermal shock stability of traditional refractory castables.
[0029] The introduction of zirconium oxide can effectively inhibit the erosion of furnace linings made of castable by slag and molten metal, improve the service life of the working lining, reduce the frequency of maintenance, save labor and time costs, and improve the production efficiency of customers. Detailed Implementation
[0030] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific implementation method, features and effects of a cementless thermal shock resistant refractory castable proposed according to the present invention are described in detail below.
[0031] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0032] For the purposes of this specification and the appended claims, unless otherwise stated, all expressions, percentages, or proportions, and other numerical values used in this specification and the appended claims, are to be understood to be modified by the term "about" in all cases. Furthermore, all scopes disclosed herein include their endpoints and can be combined independently.
[0033] In the following embodiments, the fused mullite used all met the following requirements: Al2O3 content >74.0%, SiO2 content >20.0%, and CaO content ≤0.15%; the ultrafine stabilized zirconia powder used all met the following requirements: ZrO2+HfO2 content ≥94.5%, CaO content ≤0.01%, Na2O content ≤0.02%, particle size D50 = 0.1~0.3μm, and specific surface area 12~18 m² / g; the SiO2 gel powder used all met the following requirements: SiO2 content ≥99.8%, Na2O content <0.01%, CaO content ≤0.01%, and particle size ≤38μm; the active bimodal Al2O3 powder used all met the following requirements: Al2O3 content ≥99.8%, Na2O content <0.08%, CaO content ≤0.03%, particle size D50 = 1.4 μm, and specific surface area 4.8 m² / g. The selected spherical silica powders all meet the following requirements: SiO2 content > 99.6%, CaO content < 0.03%, Na2O content < 0.05%, particle size D50 = 0.5 μm, and specific surface area 12~16 m² / g; the selected high-performance composite water-reducing agents all meet the requirement that the mass ratio of carboxylic acid polymer to admixture is 8:2.
[0034] Example 1
[0035] A cementless thermal shock resistant refractory castable, calculated by mass parts, comprises the following raw material components: 27 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 23 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 18 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 8 parts of ultrafine stabilized zirconia powder, 3 parts of SiO2 gel powder, 8 parts of active bimodal Al2O3 powder, 8 parts of spherical silica powder, 0.4 parts of high-performance composite water-reducing agent, and 5 parts of water; the high-performance composite water-reducing agent is a carboxylic acid polymer and sodium hexametaphosphate.
[0036] Example 2
[0037] A cementless thermal shock resistant refractory castable, calculated by mass parts, comprises the following raw material components: 35 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 20 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 15 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 5 parts of ultrafine stabilized zirconia powder, 5 parts of SiO2 gel powder, 10 parts of active bimodal Al2O3 powder, 5 parts of spherical silica powder, 0.6 parts of high-performance composite water-reducing agent, and 4.8 parts of water; the high-performance composite water-reducing agent is a carboxylic acid polymer and sodium citrate.
[0038] Example 3
[0039] A cementless thermal shock resistant refractory castable, calculated by mass parts, comprises the following raw material components: 25 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 30 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 25 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 5 parts of ultrafine stabilized zirconia powder, 1 part of SiO2 gel powder, 5 parts of active bimodal Al2O3 powder, 5 parts of spherical silica powder, 0.4 parts of high-performance composite water-reducing agent, and 4 parts of water; the high-performance composite water-reducing agent is a carboxylic acid polymer and polyoxyethylene polyoxypropylene glycerol ether.
[0040] Example 4
[0041] A cementless thermal shock resistant refractory castable, calculated by mass parts, comprises the following raw material components: 25 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 23 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 19 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 10 parts of ultrafine stabilized zirconia powder, 1 part of SiO2 gel powder, 7 parts of active bimodal Al2O3 powder, 10 parts of spherical silica powder, 0.6 parts of high-performance composite water-reducing agent, and 4.8 parts of water; the high-performance composite water-reducing agent is a carboxylic acid polymer and sodium citrate.
[0042] Example 5
[0043] A cementless thermal shock resistant refractory castable, calculated by mass parts, comprises the following raw material components: 27 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 24 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 17 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 10 parts of ultrafine stabilized zirconia powder, 3 parts of SiO2 gel powder, 9 parts of active bimodal Al2O3 powder, 6 parts of spherical silica powder, 0.2 parts of high-performance composite water-reducing agent, and 4.2 parts of water; the high-performance composite water-reducing agent is a carboxylic acid polymer and tripolyphosphoric acid.
[0044] Comparative Example 1: Commercially available low-cement castables
[0045] Comparative Example 2:
[0046] In this comparative example, based on Example 1, the SiO2 gel powder was replaced with calcium aluminate cement, and the contents of other components were the same as in Example 1. The preparation method was also the same as in Example 1.
[0047] Performance testing
[0048] The products from Examples 1-5 and Comparative Examples 1-2 were cast into 40×40×160mm specimens, and their post-firing strength and thermal shock resistance at different temperatures were tested. The test results are shown in the table below:
[0049] Table 1. Performance test results of Examples 1-5 and Comparative Examples 1-2
[0050]
[0051] Based on the above examples 1-5 and comparative examples 1-2, it can be concluded that the high-temperature strength and thermal shock resistance of examples 1-5 after sintering are generally superior to those of the comparative examples. From the above experimental results, it can be concluded that the cement-free thermal shock resistant refractory castable of this invention, using SiO2 gel powder and active oxide powder as a binding system, avoids the use of calcium aluminate cement in traditional castable systems, thus improving the product's refractoriness and high-temperature flexural and compressive strength. This solves the problem of shortened service life of conventional refractory castables due to low strength under high-temperature conditions.
[0052] This invention's castable adopts a cement-free design, significantly reducing the introduction of Ca impurities in the raw materials and effectively avoiding the reduction in high-temperature performance caused by the formation of low-melting phases such as calcium feldspar, tricalcium silicate, and calcium aluminum feldspar. Through the synergistic effect of active oxides such as activated alumina powder, SiO2 gel powder, and spherical silica powder, solid-phase reactions are promoted and particle packing is optimized, increasing the material's density. Combined with the toughening effect of zirconia phase transformation and its excellent chemical stability, the material's resistance to thermal shock and erosion under alternating hot and cold conditions is improved, extending the service life of high-temperature working linings, reducing maintenance frequency, saving maintenance labor and time costs, and improving the user's production and operation efficiency.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been shown above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A cement-free thermal shock resistant refractory castable, characterized in that, The raw materials include the following parts by weight: 25-35 parts of fused mullite with a particle size of 0 < ≤ 1 mm, 20-30 parts of fused mullite with a particle size of 1 < ≤ 3 mm, 15-25 parts of fused mullite with a particle size of 3 < ≤ 5 mm, 5-10 parts of ultrafine stabilized zirconia powder, 1-5 parts of SiO2 gel powder, 5-10 parts of active bimodal Al2O3 powder, 5-10 parts of spherical silica powder, and 0.2-0.6 parts of high-performance composite water-reducing agent.
2. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, It also includes 4-5 parts water.
3. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, The fused mullite contains Al2O3 content >74.0%, SiO2 content >20.0%, and CaO content ≤0.15%.
4. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, The ultrafine stabilized zirconia powder has a ZrO2+HfO2 content ≥94.5%, a CaO content ≤0.01%, and a Na2O content ≤0.02%; the particle size of the ultrafine stabilized zirconia powder is D50=0.1~0.3 μm, and the specific surface area is 12~18 m² / g.
5. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, The SiO2 gel powder has a SiO2 content ≥ 99.8%, a Na2O content < 0.01%, a CaO content ≤ 0.01%, and a particle size ≤ 38 μm.
6. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, The active bimodal Al2O3 powder has an Al2O3 content ≥ 99.8%, a Na2O content < 0.08%, and a CaO content ≤ 0.03%; the active bimodal Al2O3 powder has a particle size of D50 = 1.4 μm and a specific surface area of 4.8 m² / g.
7. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, The spherical silicon micropowder has a SiO2 content > 99.6%, a CaO content < 0.03%, and a Na2O content < 0.05%; the particle size of the spherical silicon micropowder is D50 = 0.5 μm, and the specific surface area is 12~16 m² / g.
8. The cement-free thermal shock resistant refractory castable according to claim 1, characterized in that, The high-performance composite water-reducing agent comprises a carboxylic acid polymer and an additive; the mass ratio of the carboxylic acid polymer to the additive is 8:
2.
9. The cement-free thermal shock resistant refractory castable according to claim 8, characterized in that, The carboxylic acid polymer is a comb-like copolymer with a main chain degree of polymerization of 25-45 and a side chain degree of polymerization of >45; the additive is one or more of sodium hexametaphosphate, tripolyphosphate, sodium citrate, polyoxyethylene polyoxypropylene glycerol ether, and polyoxyethylene polyoxypropylene pentaerythritol ether type polyether.